2013
DOI: 10.5713/ajas.2013.13032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbohydrate Source and Cottonseed Meal Level in the Concentrate on Feed Intake, Nutrient Digestibility, Rumen Fermentation and Microbial Protein Synthesis in Swamp Buffaloes

Abstract: The objective of this study was to investigate the effect of carbohydrate source and cottonseed meal level in the concentrate on feed intake, nutrient digestibility, rumen fermentation and microbial protein synthesis in swamp buffaloes. Four, 4-yr old rumen fistulated swamp buffaloes were randomly assigned to receive four dietary treatments according to a 2×2 factorial arrangement in a 4×4 Latin square design. Factor A was carbohydrate source; cassava chip (CC) and CC+rice bran at a ratio 3:1 (CR3:1), and fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Consistent with the present result, Wanapat et al (2013c) found that cows fed with Hipro-feed diet had a higher total feed intake. However, Wanapat et al (2012Wanapat et al ( , 2013aWanapat et al ( , 2013b did not show any difference on voluntary feed intake of beef cattle, young dairy bulls, and buffaloes by Hipro-feed feeding. The different results could be due to the difference in animal type, feeding programme, and environmental factors.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Consistent with the present result, Wanapat et al (2013c) found that cows fed with Hipro-feed diet had a higher total feed intake. However, Wanapat et al (2012Wanapat et al ( , 2013aWanapat et al ( , 2013b did not show any difference on voluntary feed intake of beef cattle, young dairy bulls, and buffaloes by Hipro-feed feeding. The different results could be due to the difference in animal type, feeding programme, and environmental factors.…”
Section: Resultsmentioning
confidence: 69%
“…This result indicated that a combination of an appropriate carbohydrate source and a high protein concentrate feed may improve rumen fermentation by providing suitable pH conditions for microorganism activity as mentioned by Hungate (1966). It was reported that cottonseed meal in the concentrate did not affect ruminal pH, NH 3 -N, or BUN concentrations (Wanapat et al 2012(Wanapat et al , 2013a(Wanapat et al , 2013b(Wanapat et al , 2013c. This could be due to the efficiency of animals to use nitrogen for microbial protein synthesis.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This finding agreed with the report of Phesatcha et al [8] who supplemented Flemingia macrophylla hay which had increased the CP and NDF digestibilities. It has been reported that CT in the feeds combined with protein to protect protein degradability in the rumen [19]. Results suggest that the CT in FMS effectively impacted the nutrient digestibility and the microbial activity in the rumen, as well as increased the rumen fermentation efficiency.…”
Section: Resultsmentioning
confidence: 90%